PERKEMBANGAN EKONOMI KREATIF DIKALANGAN GENERASI MILLENIAL MUSLIM DENGAN MELIHAT PELUANG DI KEMAJUAN ZAMAN - Rida Kartika; Muhammad Iqbal Fasa; Suharto Suharto (LP2M Universitas Bina Bangsa, 2022)
The development of cuttent development creative economy in Indonesia needs to be improved. Indonesia creative economy as a new force to the spirit of 2025 is not only limited but also to be creative with the mission statement on behalf of the cultural identity of Indonesia on any creative work created by the children of the nation. Development of the creative economy can not be separated from the younger generation as a storehouse of creativity. Young people are the productive resources with creative ideas can open a business (entrepreneurs), which also help the government in reducing the unemployment rate in the labor force. More and more young people are involved in the entrepreneurial world, the more the productivity is generated so that the impact on the increasing development of the national economy. SWOT Analysis which do generate program development of young entrepreneurs in the creative economy through culture-based training program, development and capitalization